Remediating learners with learning challenges resulting from obvious physiologically-influenced special needs in the regular classroom setting (2014)
Learning as a dynamic task requires the synergy of various factors in order for the learner to benefit from the instruction being passed. Several factors could however impede on the successful transmission of ideas, as well as effective learning, among which is the learner’s innate ability, learning style, cultural background and emotional status. Also, an important factor affecting learning is the learner’s physiological makeup - some conditions that at times could present as a special need area and would require effective management for adequate learning to transpire. The author examined how learners with physiological peculiarities could be helped to learn appropriately in the classroom setting, and their learning problems ameliorated